2008
DOI: 10.1007/s11064-008-9861-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Different Extracts from Melissa officinalis, Matricaria recutita and Cymbopogon citratus

Abstract: Considering the important role of oxidative stress in the pathogenesis of several neurological diseases, and the growing evidence of the presence of compounds with antioxidant properties in the plant extracts, the aim of the present study was to investigate the antioxidant capacity of three plants used in Brazil to treat neurological disorders: Melissa officinalis, Matricaria recutita and Cymbopogon citratus. The antioxidant effect of phenolic compounds commonly found in plant extracts, namely, quercetin, gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 61 publications
8
101
1
9
Order By: Relevance
“…Our results are slightly different from those reported by Pereira et al (2009) that found similar DPPH . inhibition for methanolic and ethanolic extracts of C. citratus and lower scavenging activity for aqueous extracts.…”
Section: Antioxidant Activitiescontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are slightly different from those reported by Pereira et al (2009) that found similar DPPH . inhibition for methanolic and ethanolic extracts of C. citratus and lower scavenging activity for aqueous extracts.…”
Section: Antioxidant Activitiescontrasting
confidence: 99%
“…It can also act as an antidepressant and as a mood enhancer. Other researches also reported hypoglycemic, hypolipidemic, anxiolytic, sedative (Blanco et al, 2009) and antiox-idant properties (Pereira et al, 2009;Figueirinha et al, 2008;Cheel et al, 2005;Cheah et al 2001).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several investigations have shown that the essential oil of C. citratus possesses antibacterial (NAIK et al, 2010), antifungal (NGUEFACK et al, 2012), antioxidant (PEREIRA et al, 2009), anti-Leishmania (MACHADO et al 2012) and insecticidal effects (KUMAR et al, 2013). These properties are attributed primarily to the major constituent of the essential oil, the citral, which is a natural combination of two isomeric aldehydes (Figure 1), neral (cis-citral) and geranial (trans-citral).…”
Section: Introductionmentioning
confidence: 99%
“…They have various physical-chemical properties and therefore optimal parameters of their extraction from plant material are different. The crude extraction of these compounds was realised by extraction solvents such as methanol, ethanol, acetone, propanol, and their water solutions (Herodež et al 2003;Javanmardi et al 2003;Dastmalchi et al 2008;Pereira et al 2009). The selection of optimal extraction solvent was made from the range of water solutions of propan-2-ol because water solutions of this organic solvent can simulate the polarity of all extraction solvents described.…”
Section: Analyses Of the Response Variablesmentioning
confidence: 99%